PENGARUH KINERJA KEUANGAN PERUSAHAAN TERHADAP PENGUNGKAPAN TANGGUNG JAWAB SOSIAL (STUDI KASUS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2011-2014) - admin, INTAN APRILIANA PUTRI B11112152 (Jurnal Manajemen Update, 2016)
Corporation in expansion must give attention to both of social aspect (people) and environment aspect be sides economics aspect (profit). The objectives of this research to know the Corporate Social Responsibility Disclosure and to analize the influence of financial performance corporate to Corporate Social Responsibility on manufactur corporate which is listed on BEI in 2011 until 2014 periods. The population of this research is 148 corporate which is listed as manufactur corporate on BEI 2014 period. The sample of this research was getting by purposive sampling method, so the sample is 17 corporate in 4 periods, but in the procces of the research, there are five corporate indicated as outlier data, so there are 12 corporate in 4 periods which is used as sample in this research. The analysis technique used is multiple linear regression analysis with SPSS 16.00. The result of this research shows that size variable has a positive but doesn’t have a significant influence to corporate social responsibility disclosure. Leverage (DER) variable has a negative and significant influence to corporate social responsibility disclosure, and profitability (ROA) variable has a negative but doesn’t have a significant influence to corporate social responsibility disclosure. Size, leverage (DER), and profitability (ROA) have an influence to corporate social responsibility disclosure simultaneously. Keywords: Corporate Social Responsibility Disclosure, Financial Performance, CSR Indeks, Corporate Size, Return On Asset, Debt To Equity Ratio.